2021
DOI: 10.1155/2021/6679348
|View full text |Cite
|
Sign up to set email alerts
|

Tongxie Anchang Decoction Relieves Visceral Hypersensitivity in Diarrhea-Predominant Irritable Bowel Syndrome Rats by Regulating the NGF/TrkA Signaling Pathway

Abstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal disease characterized by visceral hypersensitivity-related abdominal pain, in which diarrhea-predominant IBS (IBS-D) is the main subtype and has a high clinical incidence. Tongxie Anchang Decoction (TXACD) has been proved to significantly improve abdominal pain in patients with IBS-D, but its underlying therapeutic mechanism still remains unclear. In the present study, IBS-D model rats were induced by neonatal maternal separation (NMS) combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These alterations can subsequently impact visceral sensation, intestinal movement, and endocrine function. Thus, this cascade of events may contribute to the onset or exacerbation of IBS symptoms [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These alterations can subsequently impact visceral sensation, intestinal movement, and endocrine function. Thus, this cascade of events may contribute to the onset or exacerbation of IBS symptoms [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A potential mechanism might explain MDD may lead to higher IBS risk. Drossman et al, found by functional magnetic resonance imaging that depression can activate the cingulate region of the limbic system of the cerebral cortex (Drossman et al, 2003); and the emotional activity center of the limbic system is in the same anatomical site as the vegetative center and the endocrine regulatory center, which govern the movement and secretion of the digestive tract; thus, the function of the vegetative center and the endocrine regulatory center is altered, and then the information is transmitted to the enteric nervous system through the brain-gut axis, causing changes in neurotransmitters and adrenocorticotropin-releasing factors, which affect visceral sensation, intestinal movement and endocrine function (Tan et al, 2021). In addition, study has shown that depression can lead to increased levels of expression of cytokines such as IL-1 β and TNF- α in the peripheral serum of patients (Miller, Maletic, & Raison, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 60 IBS patients were enrolling in a study and were divided into the control group ( n = 20) and the treatment group ( n = 40), which were given oral pinaverium bromide tablets and Tongxie Yaofang decoction on the basis of conventional treatment, respectively. And the results reported that the flavored Tongxie Yaofang had a significant effect on the symptoms of patients with IBS-D[ 117 ], and improving the gut microbiome, alleviating visceral hypersensitivity, regulating 5-HT level in patients, and inhibiting colonic contraction are mechanisms for the treatment of IBS[ 118 - 120 ]. Moreover, Tongxie Anchang Decoction improves IBS by reducing visceral hypersensitivity, reversing mast cell infiltration, and regulating 5-HT[ 118 , 121 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…And the results reported that the flavored Tongxie Yaofang had a significant effect on the symptoms of patients with IBS-D[ 117 ], and improving the gut microbiome, alleviating visceral hypersensitivity, regulating 5-HT level in patients, and inhibiting colonic contraction are mechanisms for the treatment of IBS[ 118 - 120 ]. Moreover, Tongxie Anchang Decoction improves IBS by reducing visceral hypersensitivity, reversing mast cell infiltration, and regulating 5-HT[ 118 , 121 ]. And Xiang Sha Liu Jun Zi Decoction reduced the mean diarrhea score of IBS patients[ 122 ].…”
Section: Treatmentsmentioning
confidence: 99%